Performance Assessment of a High-Powered Boost Converter for Photovoltaic Residential Implementations - Ghaderi, Davood; Bayrak, Gokay (Elektronika ir Elektrotechnika, 2019)
This paper introduces a new boost converter operating in several duty cycles with a high powered and no transformer design for Photovoltaic residential implementations. The proposed converter is performed without any extra power switch by a voltage pre-amplifier unit between the input inductor and the power switch and is derived with a simple structure. The designed converter provides a voltage gain by 38 times for the operation of 90% of the duty cycle. This condition shows that the proposed converter has more efficient compared to the conventional boost converters. Besides, a higher amount of DC gain is possible by adding a cascade blocks connection of switched-capacitor (SC) in the converter’s output. The operational principles are evaluated to justify the utility of converter for residential PV systems in the study. Also, a 200 W powered prototype converter is implemented by applying a commercial PV panel in the laboratory. The experimental results confirm both the mathematical and simulation results.